2014
DOI: 10.1002/2013jb010351
|View full text |Cite
|
Sign up to set email alerts
|

Shallow, old, and hydrologically insignificant fault zones in the Appalachian orogen

Abstract: The permeability of fault zones impacts diverse geological processes such as hydrocarbon migration, hydrothermal fluid circulation, and regional groundwater flow, yet how fault zones affect groundwater flow at a regional scale (1-10 km) is highly uncertain. The objective of this work is to determine whether faults affect regional patterns of groundwater flow, by using radioactive radon and chloride to quantify groundwater discharge to lakes underlain by faults and not underlain by faults. We sampled lakes over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…, ; Kluge et al . , ; Malgrange & Gleeson, ). For simplicity, most studies assumed constant 222 Rn activity for the whole water column and disregarded vertical gradients related to lake stratification, although these are widely known to potentially be informative (Cook et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ; Kluge et al . , ; Malgrange & Gleeson, ). For simplicity, most studies assumed constant 222 Rn activity for the whole water column and disregarded vertical gradients related to lake stratification, although these are widely known to potentially be informative (Cook et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of 222 Rn in lakes has only gained attention in recent years, probably due to generally low 222 Rn activity in lakes (in the range of a few Bq/m 3 ), in contrast to the high activity in groundwater (typically between 1,000 and 100,000 Bq/m 3 ). The first lake water budget based on 222 Rn was demonstrated by Corbett et al (1997) and led to many subsequent applications (Cook et al, 2008;Gilfedder, Frei, Hofmann, & Cartwright, 2015;Gleeson, Novakowski, Cook, & Kyser, 2009;Kluge et al, 2007;Kluge et al, 2012;Malgrange & Gleeson, 2014). For simplicity, most studies assumed constant 222 Rn activity for the whole water column and disregarded vertical gradients related to lake stratification, although these are widely known to potentially be informative (Cook et al, 2008;Schmidt & Schubert, 2007).…”
mentioning
confidence: 99%
“…It can be questioned if other parameters, such as faulting (see also the isolated anomalies along the downmost branch of the Foulon Fault, in the eastern sector of the Bécancour watershed; Figure 3a), could locally influence the spatial distribution of helium in the basin. The previous work on the hydrogeology of the region did not find any evidence of tectonic control on the hydrodynamics of the basin [24,25,35]. However, a study of helium and methane in the groundwater from the same region, completed by Moritz et al [55], showed a rough possible relation between the concentration of 4 He and the distance to the main tectonic accidents.…”
Section: Helium Isotopic Spatial Distribution and Recharge Confinemen...mentioning
confidence: 92%
“…Larocque et al [24,25] did not identify any hydrogeological influence of the faults. Malgrange and Gleeson [35] also showed the limited influence of the Appalachian fault system on the local hydrogeology.…”
Section: Study Areamentioning
confidence: 99%